Suitable MLP Network Activation Functions For Breast Cancer And Thyroid Disease Detection. - Isa, I.S.; Saad, Z.; Omar, S.; Osman, M.K.; Ahmad, K.A.; A., H.; Sakim, Mat (2010)

(untitled)
This paper presents a comparison study of various MLP activation functions for detection and classification problems.